Web-Based Learning Media for Distance Education: A Review - Donal Nababan; Aldani Putri Wijayanti; Rico; Muhammad Nas'al Nashrallah; Wuni Arum Sekar Sari (Jurnal Penelitian Pendidikan IPA, 2023)
Learning media are all forms of tools or materials used in the learning process to help students understand and master the subject matter. This media can be in the form of physical objects, technology, or a combination of both designed to communicate information more effectively and facilitate understanding and retention of learning concepts. The learning and teaching process that uses web-based learning media for distance education is required to be independent and responsible for the learning process because one can learn anywhere, at any time. The important thing is that the tools are available. This research uses a systematic literature review method using Preferred Reporting Items for Systematic Reviews (PRISMA). The research aims to explain web-based learning media for distance education. The research results show that through web-based learning media, students can search for and retrieve information or learning materials based on the syllabus or criteria set by the teacher or education manager. Students will have a wealth of information because they can access information from anywhere related to their learning material, through web-based learning media used for distance education can be increased by using learning materials that are well-designed professionally and pay attention to and use the characteristics of characteristics of multimedia.